2004
DOI: 10.1071/eg04137
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Aeromagnetic Wavelengths of the Magnetic Signals of Ocean Swell

Abstract: Ocean swells have a magnetic signal, caused by the motional induction of seawater moving in the steady main magnetic field of Earth. These signals may be sensed by a low-flying aircraft, carrying out aeromagnetic measurements over the ocean. The apparent spatial wavelength that such signals will have, when observed data are plotted out for geological purposes, can vary greatly. It will depend particularly on the relative speeds and directions of travel of the observing aircraft and the ocean swells. The appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Lilley and Weitemeyer (2004a) calculated the apparent aeromagnetic wavelengths of the magnetic signals of the ocean swell. Lilley et al (2004b) also observed the magnetic fields generated by ocean waves near the sea surface. Semkin and Smagin (2012) investigated the effect of self-induction exhibited by the ocean wave-induced electromagnetic fields.…”
Section: Introductionmentioning
confidence: 92%
“…Lilley and Weitemeyer (2004a) calculated the apparent aeromagnetic wavelengths of the magnetic signals of the ocean swell. Lilley et al (2004b) also observed the magnetic fields generated by ocean waves near the sea surface. Semkin and Smagin (2012) investigated the effect of self-induction exhibited by the ocean wave-induced electromagnetic fields.…”
Section: Introductionmentioning
confidence: 92%
“…Ochadlick report aeromagnetic measurements in agreement with the theory of Weaver. Observations of the magnetic field disturbances of ocean waves were also reported by Fraser, Watermann and Lilley et al [6][7][8]. Garcia described a scheme for eliminating part or all of this surface wave-generated noise component based on reference data provided by signal proportional to the ocean surface [9].…”
Section: Introductionmentioning
confidence: 93%
“…Magnetometry has emerged as a promising alternative to traditional velocimetry techniques (Tyler, 2006; Tyler et al., 1997) to quantify large‐scale marine flows, including vessel wakes (Zou & Nehorai, 1998), tsunami detection and parameterization (Lin et al., 2021; Minami et al., 2021; Zhang et al., 2014), wave measurements (Davis, 1991; Podney, 1975), and ocean current profiling (Filloux, 1973; Lilley & Weitemeyer, 2004; Longuet‐Higgins et al., 1954). Instead of measuring the velocity field directly, these magnetic techniques measure the flow‐induced magnetic fields that naturally arise when electrically conductive fluids, such as seawater, move through a magnetic field, such as the Earth's geomagnetic field (Faraday, 1832; Podney, 1975; Tyler et al., 1997, 2003).…”
Section: Introductionmentioning
confidence: 99%